Store-related factors contributing to offline private label brands purchase intention among Gen Y customers - Sawanah Mumin; Phang Ing @ Grace (MAG Scholar‘s, 2021)
The purpose of this study is to examine store-related factors contributing to the purchase intention towards private label brands (PLBs) among Gen Y customers in Kota Kinabalu, Sabah. Representing one of the biggest market segments in Malaysia, Gen Y is considered more open-minded to try new products than Baby Boomers. However, retail research focusing on Gen Y, particularly their buying intention of PLBs product, is scarce. A purposive sampling technique was utilised and a total of 300 questionnaires were distributed among Gen Y shoppers aged 23-39, who frequented supermarkets and drugstores. This study generated 240 usable responses (80% response rate). All the store-related variables were found to have significant relationships with attitude towards purchasing PLBs product, which in turn, affected purchase intention. Attitude mediated the relationships between all the store-related variables and purchase intention. Product category and retail format significantly moderated the relationship between attitude and purchase intention. This study benefits academic and marketing practitioners by expanding on previous literature towards customer behaviour, which the marketing practitioners could benefit from the private label initiative as well as have a better understanding of their target customers to further enhance the sales among the Gen Y customers.